2022
DOI: 10.1002/jccs.202200234
|View full text |Cite
|
Sign up to set email alerts
|

Geometric, spintronic, and opto‐electronic properties of 3d transition metals doped silicene: An ab initio study

Abstract: This study shows density functional theory (DFT) investigations that 3d transition metals (TM) doping in silicene can greatly alter the geometric, spintronic, and optoelectronic properties of the pristine silicene (p‐Si) layer. Significant Bader charge transfer from 3d TM atoms to surrounding Si atoms ensures the tight bonding between dopant and substrate; hence, all the 3d transition metal‐doped silicene (3d TM‐Si) systems are said geometrically strong and stable. Sc‐ and Ti‐doped systems show the lowest form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…36 It has been concluded from above literature that Ti decorated hBN monolayer has been found good catalyst and gas storage material. 37,38 However, no study has been reported using Ti doped hBN monolayer as gas sensing material for CO 2 , CO, H 2 S, HF and NO. Therefore, a detailed study containing structural and electronic properties of gas adsorbed systems is an urgent need.…”
Section: Introductionmentioning
confidence: 99%
“…36 It has been concluded from above literature that Ti decorated hBN monolayer has been found good catalyst and gas storage material. 37,38 However, no study has been reported using Ti doped hBN monolayer as gas sensing material for CO 2 , CO, H 2 S, HF and NO. Therefore, a detailed study containing structural and electronic properties of gas adsorbed systems is an urgent need.…”
Section: Introductionmentioning
confidence: 99%
“…The 3d TM atoms, including V to Co doped silenes, induce magnetic moments in the system, in which Cr-, Co-, Mn- and Cu-doped silicene become half metals, Ti-doped silicene becomes an indirect semiconductor, whereas the rest others convert into metals. 188 Interestingly, Ni-doped silicene presents antiferromagnetic spin states when Ni atoms in the same lattice substitute two silicon atoms. 189 Chen et al and his team verified that silicene co-doped with both TM and N atoms can be used as a good electrode material with a large quantum capacity.…”
Section: D Materials Under Doping Engineeringmentioning
confidence: 99%
“…Spintronic devices can use magnetic semiconductors with high carrier mobility to tune the generation, transmission, and detection of spin currents. Graphene, silicene, and germanene have large carrier mobility, but their application in spintronic devices is greatly limited by the fact that they are nonmagnetic and have a zero band gap at the Fermi energy level [14–19]. Therefore, 2D materials derived from the fifth main group element (P, As, Sb, Bi) layered materials have received a lot of attention from researchers.…”
Section: Introductionmentioning
confidence: 99%